Cape Mermaid mystery - Keene, Carolyn (Keene, Carolyn. Nancy Drew and the clue crew, 2012)
"Nancy and her friends are headed for the shores of Cape Mermaid, New Jersey, where they are hoping to spend a fun-filled week. But as soon as they arrive strange things start to happen-- including a possible ghost sighting. Could the rumored ghost of Cape Mermaid actually exist? Or is there more to the story than meets the eye? It's up to the Clue Crew to find out who-- or what-- is haunting the cape"--P. [4] of cover.